Half-Sandwich Ru(II) Halogenido, Valproato and 4-Phenylbutyrato Complexes Containing 2,2'-Dipyridylamine: Synthesis, Characterization, Solution Chemistry and In Vitro Cytotoxicity - Štarha, Pavel; Trávníček, Zdeněk; Křikavová, Radka; Dvořák, Zdeněk (Molecules (Basel, Switzerland), 2016)
Halogenido and carboxylato Ru(II) half-sandwich complexes of the general composition [Ru(η⁶-p-cym)(dpa)X]PF₆ (1-5) were prepared and thoroughly characterized with various techniques (e.g., mass spectrometry, NMR spectroscopy and X-ray analysis); dpa = 2,2'-dipyridylamine; p-cym = p-cymene; X = Cl- (for 1), Br- (for 2), I- (for 3), valproate(1-) (for 4) or 4-phenylbutyrate(1-) (for 5). A single-crystal X-ray analysis showed a pseudo-octahedral piano-stool geometry of [Ru(η⁶-p-cym)(dpa)I]PF₆ (3), with a η⁶-coordinated p-cymene, bidentate N-donor dpa ligand and iodido ligand coordinated to the Ru(II) atom. The results of the ¹H-NMR solution behaviour studies proved that the complexes 1-5 hydrolyse were in the mixture of solvents used (10% MeOD-d₄/90% D₂O). Complexes 1-5 were in vitro inactive against the A2780 human ovarian carcinoma cell line, up to the highest tested concentration (IC50 > 100 μM).
Keywords: in vitro cytotoxicity; half-sandwich; Molecular Structure; Models, Molecular; X-ray structure; protonová magnetická rezonanční spektroskopie; Antineoplastic Agents; lidé; Solvents; racionální návrh léčiv; Crystallography, X-Ray; rozpouštědla; solution behaviour; Ruthenium; glutathion; Neoplasms; 2,2′-dipyridylamine; molekulární modely; Humans; nádory; krystalografie rentgenová; nádorové buněčné linie; molekulární struktura; protinádorové látky; Drug Design; Proton Magnetic Resonance Spectroscopy; Glutathione; ruthenium; Cell Line, Tumor